2023
DOI: 10.1177/09564624231215151
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate usage of post-exposure prophylaxis-in-pocket for HIV prevention by individuals with low-frequency exposures

Matthew Clifford Rashotte,
Deborah Yoong,
Mark Naccarato
et al.

Abstract: PEP-In-Pocket (Post-Exposure Prophylaxis-In-Pocket, or “PIP”) is a biobehavioural HIV prevention strategy wherein patients are proactively identified and given a prescription for HIV post-exposure prophylaxis (PEP) medications to self-initiate in case of high-risk exposures. We evaluated this strategy in a prospective observational study at two hospital-based clinics in Toronto, Canada. HIV-negative adults using PIP underwent chart review and completed quarterly electronic questionnaires over 12 months. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Salience Theory) and provision of patient autonomy, which could increase patient satisfaction and retention. For example, a 12-month follow-up of PIP participants ( n = 25) showed a high satisfaction and a preference for PIP over other service modalities [95]. Similarly, a recent randomized control trial in Africa demonstrated, allowing patients ( n = 403) to choose between PrEP and PEP could double care retention time [96 ▪ ].…”
Section: Evolving the Canadian ‘Pip’ Model: Broader Implications For ...mentioning
confidence: 98%
“…Salience Theory) and provision of patient autonomy, which could increase patient satisfaction and retention. For example, a 12-month follow-up of PIP participants ( n = 25) showed a high satisfaction and a preference for PIP over other service modalities [95]. Similarly, a recent randomized control trial in Africa demonstrated, allowing patients ( n = 403) to choose between PrEP and PEP could double care retention time [96 ▪ ].…”
Section: Evolving the Canadian ‘Pip’ Model: Broader Implications For ...mentioning
confidence: 98%